Aplikasi Web Cek Riska sebagai Upaya Meningkatkan Pengetahuan Ibu Mendeteksi Dini Risiko Tinggi Kehamilan - Ni Luh Putu Martini; Irna Nursanti; Giri Widakdo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aimed to determine the effect of the risk checks web application on the knowledge of mothers to detect high risk early in pregnancy. The research design used in this study was a quasi-experimental design with one group design without control. The results showed that the mean difference before and after the intervention was 13.00, with a p-value of 0.000. In conclusion, the risk check web application can increase mothers' knowledge to detect high risk early in pregnancy. Keywords: Web Application, High-Risk Pregnancy